2016
DOI: 10.1038/pcan.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Common variation in BRCA1 may have a role in progression to lethal prostate cancer after radiation treatment

Abstract: Purpose To evaluate if single-nucleotide polymorphisms (SNPs) reflecting common variation in the tumor suppressor BRCA1 affects prostate cancer (CaP) outcomes. Because radiation therapy (RT) induces DNA damage, we hypothesized that common variation in BRCA1 plays a role in progression to lethal CaP, particularly in patients receiving RT. Methods We followed 802 men diagnosed with localized CaP (cT1-T3/N0/M0) who were treated with RT in the US Health Professionals Follow-up Study (HPFS) and Physicians’ Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Among the eight single nucleotide polymorphisms (SNP) of the BRCA1 gene, the rs799923, rs1799966 and rs799917 have been associated with the increased risk of BC in Asians [ 22 , 23 ]. In contrast, the rs16942 and rs1799949 variants have been associated with the predisposition to BC in the African population [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight single nucleotide polymorphisms (SNP) of the BRCA1 gene, the rs799923, rs1799966 and rs799917 have been associated with the increased risk of BC in Asians [ 22 , 23 ]. In contrast, the rs16942 and rs1799949 variants have been associated with the predisposition to BC in the African population [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as markers of radiotoxicity, identification of patients less likely to respond to radiation would guide decision making early on in the curative treatment pathway for localised PrCa. In a study of common variants of the BRCA1 gene in men who underwent definitive treatment for localised PrCa, two BRCA1 SNPs were found to have a significant association with lethal PrCa after RT:[44] rs4474733 was associated with a 35% lower risk of lethal PrCa and rs8176305 was associated with a two-fold increased risk of lethal PrCa. There was no significant association observed in men treated with surgery.…”
Section: Common Variants and Precision Medicinementioning
confidence: 99%
“…Three studies were identified for the UK: one included patients with PC [24], one included mCRPC [6] and one included primary PC [30]. 12 studies were identified for the USA: four included PC [35,38], four included mCRPC [39,40,44] (one of which also required patients to express androgen receptor variant 7) [43], one included mPC [46], one included both primary PC and CRPC [48] and two included primary PC [50,51]. Three studies were multinational: two included mCRPC [53,55] and one included CRPC [59].…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Of the 26 included studies, interventions were separated into drug-based treatments (12 studies) [6,17,18,20,39,40,43,44,46,53,55,57], non-drug-based treatments (11 studies) [14,19,21,22,30,34,[36][37][38]50,51] and mixed treatments (three studies) [15,24,48].…”
Section: Treatments Identifiedmentioning
confidence: 99%